What is gene profiling contributing to the characterization of chronic lymphocytic leukemia (Hematology Meeting Reports, 2009)
Gene profiling is a technology that allows to assess simultaneously the levels of expression of thousands of genes in a given cell sample using a single chip. This revolutionary technology has witnessed important applications in the study of acute and chronic hematologic malignancies. These can impact on the diagnostic work-up, on the prognostic stratification, on the correlation with the response to treatment and on the design of innovative therapeutic strategies, as well as on a better understanding of the biologic properties of the leukemic cells and of the non-neoplastic accessory cell populations. This innovative technology has been successfully applied to the study of CLL.